Upaya Pelestarian Permainan Tradisional Melalui Pemberdayaan Peserta Didik MI Asy-Syifa di Kelurahan Surabaya Kecamatan Sungai Serut Kota Bengkulu - Yuhaswita Yuhaswita; Edi Gunawan; Nafisah Nafisah (UIN Fatmawati Sukarno Bengkulu, 2024)
Traditional games are an integral part of cultural heritage that needs to be preserved and promoted to maintain its identity and continuity. The purpose of this study is to identify efforts to preserve traditional games through the empowerment of students at Asy-Syifa Madrasah Ibtidaiyah (MI) in Surabaya sub-district, Sungai Serut District, Bengkulu City. The research method employed is qualitative with a case study approach. Data was collecting through observation, interview and documentation. The research findings indicate that MI Asyifa Syifa has made many efforts to preserve traditional games, including conducting active and experiential learning activities, teacher training, and collaboration with local communities. Empowering students by active participation in these activities also contributes to their understanding of the need of preserving cultural heritage. However, further efforts are still needed to enhance public awareness and participation in preserving traditional games to ensure the continuity of local culture in the future.